Feed Formulation in Broiler Chickens Based on Standardized Ileal Amino Acid Digestibility - Hoehler, Dirk; Lemme, A.; Ravindran, V.; L. Bryden, W.; S. Rostagno, H. (Avances en Nutrición Acuicola, 2019)
Analysis of ileal contents rather than excreta is a more reliable method for assessing amino acid digestibility in poultry. Debate will continue among nutritionists about the relative merits of apparent and true digestible amino acid systems. However, there is no doubt that all digestible amino systems are superior to the use of total amino acids in feed formulations. Present methods of evaluating amino acid availability have specific applications and shortcomings. Standardized ileal digestibility is discussed as the concept of choice and some areas for future research are highlighted. Performance data in growing broiler chicks demonstrate the advantages of feed formulation based on standardized ileal digestibility of amino acids in feed ingredients.